FEATURES OF SOCIAL ADAPTATION OF ADOLESCENTS WITH MENTAL DISORDERS - Turayev Bobir Temirpulotovich, Ibragimova Muazam Holdorovna , Ortiqova Sohiba Xamro qizi (Journal of Science in Medicine and Life, 2024)
Currently, due to the medical, personnel and socio-economic aspects in the development of Health Care, great importance is attached to saving the mental health of the younger generation. Mental disorders starting at an early age negatively affect the developing psyche and personality, which complicates the processes of socialization.